Performance of groundnut (Arachis hypogea) and mungbean (Vigna radiata) on tin tailings in Malaysia - Juhari, Rahman; Yaccob, Othman (Universiti Pertanian Malaysia, 1979)
Tin tailings are tracks of artificially created wasteland as a result of mining activities, and generally consist of sand and slime tailings (maene et al. 1975). Early studies of Brickenshaw (1931) and k1itchell (1959) indicate that these tailings are completely devoid of humus} organic matter and nitrogen. Furthermore their physical and chemical properties are not normally conducive to plant growth without soil amendments. with these limitations cheaper methods of using these (soils' for food crop production must be found. Selection of suitable crops may, therefore, be more desirable If cropping on tin tailings is to be attempted.